EtherCAT Technology for Reliable Industrial Communication Networks - Rutagangibwa, Vincent (IJSRD - International Journal for Scientific Research & Development, 2015)
Abstract— The modern developing communication industry requires increasingly faster, more throughput and reliable com-munication networks which are able to work in a hard real-time situation. This paper presents the EtherCAT communication technology that does not only meet the above requirements but also allows market to reduce implementation costs in order to have affordable and reliable services. The paper further explains the EtherCAT operation principles with the most important mechanisms such as Frame processing on-the-fly, logic ring topology and slave synchronization among other mechanisms. The comparison of EtherCAT with the traditional most pop-ular industrial based networks is also presented to show the leading position of this upcoming technology in the Industrial communication networks in terms of reliability, performance, implementation and cost.
Keywords: EtherCAT; Communication Networks; Indus-trial Automation